A Model for Preventing Indonesian Migrant Workers from Human Trafficking Under the Guise of Digital Job Placement in Cambodia Based on Human Rights Protection - Komang Saptapramana; Zulkarnein Koto; Kif Aminanto (Indonesian Journal Publisher, 2026)
The development of digital technology has given rise to a transformation in the crime of human trafficking against Indonesian migrant workers through the mode of illegal digital job placement to Cambodia, integrated with cybercrime, scam centers, and online gambling. This study aims to analyze the crime of human trafficking under the guise of digital job placement against Indonesian migrant workers in Cambodia, examine the problems and weaknesses of legal policies in its prevention, and formulate the reconstruction and legal reform of the prevention model based on human rights protection. This study uses a normative juridical method with a legislative approach and a conceptual approach through an analysis of Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking, Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, the Law on Information and Electronic Transactions, and international legal instruments related to human trafficking and human rights. The results of the study indicate that the national legal system still faces various weaknesses in the form of regulatory disharmony, weak supervision of digital recruitment, suboptimal cross-agency coordination, minimal cyber surveillance, and the absence of a digital technology-based early warning system for trafficking. Therefore, legal reconstruction and reform are needed through strengthened cyber patrols, AI-based recruitment monitoring, cross-agency data integration, digital platform oversight, increased public digital literacy, and strengthened bilateral cooperation between Indonesia and Cambodia to create an adaptive, responsive, and human rights-based protection system for Indonesian migrant workers against the threat of modern digital human trafficking.